2017 Kansas Summer Annual Forage Hay and Silage Variety Trial - J. D. Holman; A. Obour; A. Esser; J. Lingenfelser; S. Maxwell; T. Roberts; G. F. Sassenrath (Kansas Agricultural Experiment Station Research Reports, 2018)
The 2017 summer annual forage variety trials were conducted across Kansas near Garden City, Hays, Mound Valley, and Scandia. All sites evaluated included hay and silage entries. Companies were able to enter varieties into any possible combinations of research sites, so not all sites had all varieties. Across the sites, a total of 61 hay varieties and 66 silage varieties were evaluated. The objectives of the Kansas Summer Annual Forage Variety Trial are to evaluate the performance of released and experimental varieties, determine where these varieties are best adapted, and increase the visibility of summer annual forages in Kansas. Breeders, marketers, and producers use data collected from the trials to make informed variety selections. The Summer Annual Forage Trial is planted at locations across Kansas based on the interest of those entering varieties into the test.
Keywords: summer forage; hay; silage; variety trial